Assessing maintenance strategies for cutting tool replacements in mechanized tunneling using process simulation. Issue 1 (1st February 2017) - Conrads, Alena; Scheffer, Markus; Mattern, Hannah; König, Markus; Thewes, Markus
Abstract: In mechanized tunneling, detailed planning with an accurate performance prediction of the tunnel boring machine (TBM) is needed for a successful tunnel project. Undersized logistical components, disturbances of the supply chain, as well as negligence of maintenance schedules reduce the TBM performance and frequently lead to avoidable times of standstill. This paper presents a performance forecast model for mechanized tunneling projects focusing on wear and maintenance processes of the cutting tools. The developed simulation model has been implemented in the simulation environment AnyLogic using the multi-method approach, including agent-based modeling as well as discrete-event and system dynamic simulation. The model can be used to evaluate different maintenance strategies for a tunneling project. Thus, an improved maintenance strategy for reducing the time of standstill can be found.